Editor's Choice – Carotid Stenosis Treatment: Variation in International Practice Patterns. (April 2017) - Venermo, M.; Wang, G.; Sedrakyan, A.; Mao, J.; Eldrup, N.; DeMartino, R.; Mani, K.; Altreuther, M.; Beiles, B.; Menyhei, G.; Danielsson, G.; Thomson, I.; et al.
Abstract : Objectives: The aim was to determine current practice for the treatment of carotid stenosis among 12 countries participating in the International Consortium of Vascular Registries (ICVR). Methods: Data from the United States Vascular Quality Initiative (VQI) and the Vascunet registry collaboration (including 10 registries in Europe and Australasia) were used. Variation in treatment modality of asymptomatic versus symptomatic patients was analysed between countries and among centres within each country. Results: Among 58, 607 procedures, octogenarians represented 18% of all patients, ranging from 8% (Hungary) to 22% (New Zealand and Australia). Women represented 36%, ranging from 29% (Switzerland) to 40% (USA). The proportion of carotid artery stenting (CAS) among asymptomatic patients ranged from 0% (Finland) to 26% (Sweden) and among symptomatic patients from 0% (Denmark) to 19% (USA). Variation among centres within countries for CAS was highest in the United States and Australia (from 0% to 80%). The overall proportion of asymptomatic patients was 48%, but varied from 0% (Denmark) to 73% (Italy). There was also substantial centre level variation within each country in the proportion of asymptomatic patients, most pronounced in Australia (0–72%), Hungary (5–55%), and the United States (0–100%). Countries with fee for service reimbursement had higher rates of treatment in asymptomatic patients than countries with population based reimbursement (OR 5.8, 95% CI 4.4–7.7). Conclusions: Despite evidence about treatment options for carotid artery disease, the proportion of asymptomatic patients, treatment modality, and the proportion of women and octogenarians vary considerably among and within countries. There was a significant association of treating more asymptomatic patients in countries with fee for service reimbursement. The findings reflect the inconsistency of the existing guidelines and a need for cooperation among guideline committees all over the world.